2015
DOI: 10.1016/j.anifeedsci.2015.05.023
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cinnamaldehyde, monensin and quebracho condensed tannin on rumen fermentation, biohydrogenation and bacteria in continuous culture system

Abstract: Please cite this article in press as: Ishlak, A., et al., The effects of cinnamaldehyde, monensin and quebracho condensed tannin on rumen fermentation, biohydrogenation and bacteria in continuous culture system. Anim. Feed Sci. Tech. (2015) b s t r a c tThe objective of this experiment was to evaluate the effects of different feed additives (cinnamaldehyde, monensin, and quebracho condensed tannin extract) on fermentation, trans fatty acids (FA) formation and selected strains of rumen bacteria. Four continuou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
36
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 56 publications
7
36
1
Order By: Relevance
“…Similarly, tannins decreased abundances of B. proteoclasticus and increased B. fibrisolvens (Ishlak et al . ) in vitro , which is consistent with VA accumulation as observed by Vasta et al . ().…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similarly, tannins decreased abundances of B. proteoclasticus and increased B. fibrisolvens (Ishlak et al . ) in vitro , which is consistent with VA accumulation as observed by Vasta et al . ().…”
Section: Discussionsupporting
confidence: 92%
“…) or increased (Ishlak et al . ) the abundance of B. fibrisolvens in vitro , which could explain changes in the profile of BH products in the rumen (Lourenço et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that the effects of tannins on BH might be dose‐dependent and that there are interactions between the tannin type and the dose used . Commercial tannin extract from quebracho seems to be more active on BH at lower doses and its effects disappear when included at 80 g kg −1 DM, which might explain the absence of effect at 100 g kg −1 DM reported by us and by other authors . Also, the effects of GS and CH on BH were described to be tendentiously attenuated at higher doses although not disappearing completely at 80 g kg −1 DM .…”
Section: Discussionmentioning
confidence: 66%
“…12,13 Commercial tannin extract from quebracho seems to be more active on BH at lower doses and its effects disappear when included at 80 g kg −1 DM, 12 which might explain the absence of effect at 100 g kg −1 DM reported by us and by other authors. 26 Also, the effects of GS and CH on BH were described to be tendentiously attenuated at higher doses although not disappearing completely at 80 g kg −1 DM. 12 In our experiment, CH was ineffective at 100 g kg −1 DM but GS was highly effective at even a higher dose, considering that we used purified grape seed extract.…”
Section: Discussionmentioning
confidence: 97%
“…In our trial, cinnamon oil (330 mg/L rumen fluid) did not change rumen lipid metabolism. Recently an in vitro study using a continuous culture system showed that cinnamaldehyde (400 mg/L) increased cis and trans C18:1 at the expense of C18:0, a slight increase in C18:3c9c12c15 and in C18:2c9c12 being found [17]. Taken together, these three studies are not conclusive, and it is likely that differences between them cannot be explained only by the dose of additive, by the difference between cinnamon oil and cinnamaldehyde, or by the difference in fermented substrate.…”
Section: Cinnamon Oilmentioning
confidence: 99%